(untitled) (Journal of Educational Sciences, 2023)
The article presents the work of a social pedagogue in the direction of psychological support of school students with disabilities. Integrative technology aimed at maximizing the realization of a favorable psychological climate for students with disabilities includes the following aspects: areas of psychological support and support, psychological adaptation, planned implementation results. The article describes the experience of psychological support of children with disabilities in school conditions. The article highlights the scientific works of leading scientists who have dealt with this issue. In the development and provision of the route of psychological support, the ways of interaction between teachers, a psychologist, a social pedagogue, school medical staff and parents of children with disabilities were considered. Based on the identified problems, a program of experimental pedagogical work was built, where new methods and Internet resources of psychological support were used. Measures were carried out that contributed to the elimination of obstructive problems and presented the dynamics of improving the psychological climate in building constructive relationships. At the same time, the content of the article notes that there are not enough specialists working with children with disabilities, since it is difficult to comprehend and understand all the subtleties of new knowledge in this direction. Additionally, the article describes the system of work on inclusive education, where special specialists-speech therapists, speech pathologists, oligophrenopedagogues, social educators, psychologists are retrained. Key words: inclusive education, children with disabilities, children with special educational needs, psychological support.